Development of Learning Resources: Stance of Elementary Teachers - Baterna, Cherrin E. (International Journal of Research in Interdisciplinary Studies, 2024)
This phenomenological study explored the experiences of teachers in developing learning resources in Kaputian District, Division of Island Garden City of Samal (IGACOS). This also investigated their coping mechanisms from the challenges they encountered, and their insights drawn from the findings of this study. Qualitative – phenomenological study was employed in exploring the views of the ten (10) elementary teachers of which primary instrument of data gathering was through in- depth interview. Major findings indicated that the experiences of teachers in developing learning resources included using printed learning resources, maximizing electronic or digital resources, and challenges in learning resource development. Likewise, navigating the intricate landscape of education, teachers encounter a myriad of challenges in the development of learning resources, prompting the exploration of coping mechanisms essential for their professional resilience. The major themes were adaptability and flexibility, collaboration and professional development, and student-centered approaches. For the insights, the major themes were technology integration and digital literacy, differentiated instruction and inclusivity, and assessment and feedback strategies. The research implications concerning the development of learning resources for learners are multifaceted, carrying significant weight in shaping educational practices and outcomes. As the landscape of education continues to evolve, understanding these implications becomes crucial for educators, policymakers, and researchers alike. The findings from research in learning resource development can provide insights into effective instructional strategies, the impact of technology integration, and the importance of considering diverse learning styles.